Rationalizing the greater city. The 1919 international competition for Greater Paris. (2nd January 2017) - Fernandez Agueda, Beatriz
ABSTRACT: The 1919 Greater Paris competition was the first attempt at metropolitan planning in France. Paris was then the fourth largest city in the world. As in other metropolises, congestion and hazardous urban growth were its main problems. The need of planning was evident. However, the long-term city–suburb conflict, the legal constraints, and the political divergences hindered the realization of a comprehensive plan. In this context, an international competition was launched. The prize-winner was the French architect Léon Jaussely. Although Greater Paris competition did not result in a comprehensive plan straightaway, it constitutes a turning point in Paris's planning history. Through research on unpublished sources preserved in different Parisian archives, this paper aims firstly to reconstruct the process of the competition. The thorough reports of the jury offer an entirely new approach to the study of this kind of competition, since they allow us to comprehend the preoccupations of the administrations in charge. Secondly, it intends to examine the projects, connecting their solutions with international models and debates. It focuses on those concerning the comprehensive plan and particularly on Jaussely's awarded project. Finally, the long-term influence of the competition will be discussed and regarded within the international context.